1996
DOI: 10.1159/000227559
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of c-ErbB-2 Protein in Gastric Cancer by Immunohistochemical Stain

Abstract: An immunohistochemical stain to the c-ErbB-2 protein was performed in 225 paraffin-embedded tissue blocks from patients with locally advanced gastric cancer who underwent curative resection. The overexpression of the c-ErbB-2 protein was observed in 27.4% of the patients. The c-ErbB-2 positivity showed a statistically significant correlation with nodal status and stage. The patients with an overexpression of the c-ErbB-2 protein had a tendency to a shorter survival than those without, but it was not statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 12 publications
2
13
1
1
Order By: Relevance
“…(25) 126 (29) 17 (27) 125 (29) Extended gastrectomy 8 (13) 48 (11) 8 (13) 48 (11) Bormann type 0.32 0.41 IV 5 (8) 58 (13) 5 (8) 55 (13) In previous studies, the overall frequency of ERBB2 overexpression in gastric cancer ranged from 7 to 53%. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] This wide range of overexpression of ERBB2 might be explained by the study cohort, localization within the stomach, histological subtype or interpretation of results. ERBB2 positivity is significantly higher in intestinal histology (34%) and gastro-esophageal tumors (34%) than in diffusetype (6%) and gastric locations (20%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(25) 126 (29) 17 (27) 125 (29) Extended gastrectomy 8 (13) 48 (11) 8 (13) 48 (11) Bormann type 0.32 0.41 IV 5 (8) 58 (13) 5 (8) 55 (13) In previous studies, the overall frequency of ERBB2 overexpression in gastric cancer ranged from 7 to 53%. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] This wide range of overexpression of ERBB2 might be explained by the study cohort, localization within the stomach, histological subtype or interpretation of results. ERBB2 positivity is significantly higher in intestinal histology (34%) and gastro-esophageal tumors (34%) than in diffusetype (6%) and gastric locations (20%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that ERBB2 is a poor prognostic factor in gastric carcinoma. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, Grabsch et al, 35 Kim et al, 37 and Barros-Silva et al 38 reported that ERBB2 is not associated with prognosis in large series consisting of 924, 248, and 463 patients, respectively. The disagreement is probably related to differences in sample size, patient characteristics, and interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tateishi et al (18) did not detect significant difference in the 5-year survival rates of HER-2 positive and negative patients. Lee et al (22) determined that 27.4% of 225 patients who underwent locally advanced curative gastric resection showed increased HER-2 expression and that there was no significant difference in overall survival between HER-2 positive and negative groups. Sasano et al (23) reported the HER-2 expression rate as 27%, but there was no correlation with prognosis.…”
mentioning
confidence: 99%
“…For erbB2 protein, positive rates for erbB2 immunoreactivity range from 10 to 50% for the human gastric cancers that have been studied, and is higher for welldierentiated gastric cancers (Kameda et al, 1990;Lee et al, 1996;Motojima et al, 1994;Orita et al, 1997;Uchino et al, 1993;Yonemura et al, 1991a). The expression of erbB2 protein is a signi®cant independent risk factor for long term survival, disease recurrence and lymph-node metastasis (Lin et al, 1995;Motojima et al, 1994;Orita et al, 1997;Sanz-Ortega et al, 2000;Yonemura et al, 1991a).…”
Section: Protein Localization By Immunohistochemistrymentioning
confidence: 99%